Effect of ß-mannanase supplementation and feed presentation on carcass characteristics and macro-mineral digestibility of growing rabbits fed palm kernel based diets (2012)
The influence of ß -mannanase supplementation and feed presentation of palm kernel cake (PKC, based diets were assessed on grower rabbits. Twenty crossbred grower rabbits (757.5 ± 65 g) of mixed sex aged between eight to ten weeks old were used during the trial in 2 X2 factorial design conducted in a completely randomized experimental design giving four treatment interactions with five replicates of one rabbit per replicate. The treatments were; TI- diet in mash form without enzyme; T2- diet in pellet form without enzyme; T3- diet in mash form with ß-mannanase (0.5g/kg) and T4- diet in pellet form with mannanase (0.5g/kg). The trial lasted for six weeks. The animals were weighed individually at the beginning of the study and weekly thereafter. At the end of the study period the feacal samples were collected and animals were slaughtered and measurements taken from the carcasses. The carcass yield showed no interaction, though full GIT weights (g) were significantly influenced (Tl-23.04, T2-17.67, T3-19.99 and T4- 18.74. Enzyme inclusion and feed form elicited significant effects on carcass characteristics, with varying improvements observed Enzyme inclusion on the mash diet gave lower organ weights compared to other diets. Feed form and enzyme inclusion influenced lengths of the Segments of the GTT, with rabbit on Diet 3 having the longest length. Pelleting influenced ileum lengths positively. Rabbits fed pelleted or mash diets whether supplemented or non-supplemented with ß-mannanase digested dry matter, calcium, phosphorus and magnesium in the same level. In conclusion, supplementation of diets with ß-mannanase and pelleting of diets improved phosphorus digestibility in palm kernel cake based diets. In addition, rabbits feed mash and pelleted rations with addition of ß-mannanase had improved loins as opposed to those fed mash and non-supplemented rabbits while other carcass and visceral organ characteristics were not significantly affected.